39th Aerospace Sciences Meeting and Exhibit 2001
DOI: 10.2514/6.2001-737
|View full text |Cite
|
Sign up to set email alerts
|

Compact, high-power synthetic jet actuators for flow separation control

Abstract: Although strong potential of synthetic jets as flow separation control actuators has been demonstrated in the existing literature, there is a large gap between the synthetic jet actuators (SJA) used in laboratory demonstrations and the SJAs needed in realistic fullscale applications, in terms of compactness, weight, efficiency, control authority and power density. In most cases, the SJAs used in demonstrations are either too large or too weak for realistic applications. In this work, we present the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…However, it is important to state that initially, due to the difficulty of making walls to separate the flow within the jet exit, only the plenum for each individual piston was separated from each other (see figures 2.18 and 2.19). Preliminary results with this configuration showed that there were still strong interactions between the jets generated by each piston, which were detrimental for the performance of the actuator (Gilarranz and Rediniotis, 2001b). This required the separating walls included in the plenum of the actuator to be extended up to the slot exit, as shown in figures 2.19 and 2.20.…”
Section: Second Generation High-power Synthetic Jet Arravmentioning
confidence: 99%
“…However, it is important to state that initially, due to the difficulty of making walls to separate the flow within the jet exit, only the plenum for each individual piston was separated from each other (see figures 2.18 and 2.19). Preliminary results with this configuration showed that there were still strong interactions between the jets generated by each piston, which were detrimental for the performance of the actuator (Gilarranz and Rediniotis, 2001b). This required the separating walls included in the plenum of the actuator to be extended up to the slot exit, as shown in figures 2.19 and 2.20.…”
Section: Second Generation High-power Synthetic Jet Arravmentioning
confidence: 99%
“…Synthetic jet actuators (SJA) provide a novel means of applying flow control and their potential application for the effective delay of boundary layer separation on aircraft has been the focus of intense research in recent years (Smith and Glezer, 1998;Crook and Wood, 2001;Gilarranz and Rediniotis, 2001;Glezer and Amitay, 2002). One of the reasons for this is due to their unique ability to impart additional momentum on a fluid region from which it was originally synthesised without a net mass addition, therefore requiring no bleed air supply and complex piping.…”
Section: Introductionmentioning
confidence: 99%
“…5 Half width (diameter) of jet d 1 Inner diameter of annular slot d 2 Outer Figure 1 shows a schematic view of a jet nozzle with an annular synthetic jet actuator. Figure 1(a) is a cross section of the actuator.…”
Section: Nomenclature Dmentioning
confidence: 99%
“…In recent years, a synthetic jet actuator has been shown to be a useful tool for flow control, especially separation control (1) (2) and flow vectoring (3) . A synthetic jet actuator known also as a zero net-mass-flux actuator produces an alternating flow through a slot or an orifice.…”
Section: Introductionmentioning
confidence: 99%